Anti-inflammatory Effects of Homotaurine in Patients With Amnestic Mild Cognitive Impairment - Bossù, Paola; Salani, Francesca; Ciaramella, Antonio; Sacchinelli, Eleonora; Mosca, Alessandra; Banaj, Nerisa; Assogna, Francesca; Orfei, Maria Donata; Caltagirone, Carlo; Gianni, Walter; Spalletta, Gianfranco (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a fatal dementing neurodegenerative disease, currently lacking an efficacious disease-modifying therapy. In the last years, there has been some interest in the use of homotaurine as a potential therapeutic compound for AD, but more work is still needed to prove its efficacy as disease modifier in dementia. Since inflammation is believed to play a key role in AD development, we sought to investigate here the in vivo homotaurine effect on inflammatory response in patients at the earliest stages of AD, i.e. suffering from amnestic mild cognitive impairment (aMCI). Thus, the present study aims to evaluate the effects of homotaurine supplementation on cytokine serum levels and memory performances in MCI patients. Neuropsychological, clinical, and cytokine assessment was performed at baseline (T0) and after 1 year (T12) of homotaurine supplementation in 20 patients categorized as carriers (n=9) or no carriers (n=11) of the ε4 allele of the APOE gene, the strongest genetic risk factor for AD. The serum levels of the pro-inflammatory mediators IL-1β, TNFα, IL-6 and IL-18, contextually with the anti-inflammatory molecules IL-18 binding protein (IL-18BP) and TGFβ, were analyzed to explore significant differences in the inflammatory status between T0 and T12 in the two APOE variant carrier groups. No significant differences over time were observed in patients as for most cytokines, except for IL-18. Following homotaurine supplementation, patients carrying the APOEε4 allele showed a significant decrease in IL-18 (both in its total and IL-18BP unbound forms), in turn associated with improved short-term episodic memory performance as measured by the recency effect of the Rey 15-word list learning test immediate recall. Thus, homotaurine supplementation in individuals with aMCI may have a positive consequence on episodic memory loss due, at least in part, to homotaurine anti-inflammatory effects. This study strongly suggests that future research should focus on exploring the mechanisms by which homotaurine controls brain inflammation during AD progression.